NEW METHODS OF TEACHING ENGLISH IN TECHNICAL DIRECTIONS - Azizova Muharram Rashitovna (Web of Journals Publishing, 2024)
The development of a didactically organized set of games is necessary, since the effectiveness of solving dissertation research problems depends on it. Selecting a set of games will make it possible to solve problems such as correcting errors and overcoming difficulties in the process of forming a communicative culture for students in grades 2-4.
Keywords: Pedagogical, certain game, culture, demonstration, explanatory-illustrative, training, gaming, communicative.